A case of frost branch angitis in pregnancy : an unusual presentation - Wadhwani, Meenakshi; Gogia, Varun; Kakkar, Ashish; Satyapal, Raji; Venkatesh, Pradeep; Sharma, Yograj (Nepalese Journal of Ophthalmology, 2014)
Introduction: Frosted branch angiitis usually occurs in children and presents with severe sheathing of all retinal vessels mimicking the appearance of frosted branches of a tree. Objective: To report a case of frosted branch angiitis in a pregnant lady. Case: We, hereby, report a case of a 24-year-old pregnant female who presented to us with the complaints of sudden diminution of vision in the right eye for three days. Fundus examination revealed severe sheathing of all retinal vessels with neurosensory retinal detachment suggestive of frosted branch angiitis. The case was treated with posterior sub-tenon injection of triamcinolone. Conclusion: Similar to the good prognosis reported earlier in most patients with frosted branch angiitis, the outcome in our patient was satisfactory. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11715 Nepal J Ophthalmol 2014; 6 (12): 234-236